Performance Comparison of Wheeled Soccer Robot Frames Using Finite Element Analysis (FEA) - Wibisana, Anugerah; Muhammad Imron Shodiq; Muhammad Naufal Airlangga Diputra; Naurah Nazhifah (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Negeri Batam, 2025)
Frame analysis plays a vital role in the Indonesian Wheeled Soccer Robot Contest (KRSBI-B) by identifying design weaknesses and enabling optimization before building the physical robot. This study compares three frame designs: standard, modified standard, and the Tech United team's frame. Using Finite Element Analysis (FEA) in SolidWorks, each design is tested under vertical (25 kg) and horizontal (80 kg) loads, simulating real competition conditions. The Tech United frame shows the best performance, with stress values of 5.8 MPa (vertical) and 180.0 MPa (horizontal), minimal displacements of 0.018 mm and 1.806 mm, and FOS values of 9.5 and 0.3, respectively. It also displays superior stiffness, stability, and a controlled damage zone where deformation is intentionally localized to absorb impact. These characteristics make the Tech United frame the most durable and reliable option, improving overall robot performance and ensuring it can withstand the demands of competition.